2018
DOI: 10.1038/s41467-018-06597-0
|View full text |Cite
|
Sign up to set email alerts
|

Quasicrystal nucleation and ℤ module twin growth in an intermetallic glass-forming system

Abstract: While quasicrystals possess long-range orientational order they lack translation periodicity. Considerable advancements in the elucidation of their structures and formative principles contrast with comparatively uncharted interrelations, as studies bridging the spatial scales from atoms to the macroscale are scarce. Here, we report on the homogeneous nucleation of a single quasicrystalline seed from the undercooled melt of glass-forming NiZr and its continuous growth into a tenfold twinned dendritic microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…That is, the presence of such crystallographic defects causes the spiral growth form. While screw dislocation‐driven growth has been reported in diverse areas of crystallization—and indeed extensions of the Burton–Cabrera–Frank spiral growth model exist—our proposed mechanism on the role of “hidden” polytetrahedral phases in assisting heterogeneous nucleation supports and expands upon recent reports, for instance, metastable quasicrystal‐induced nucleation yielding grain‐refined alloys, among other two‐step solidification pathways.…”
Section: Resultssupporting
confidence: 70%
“…That is, the presence of such crystallographic defects causes the spiral growth form. While screw dislocation‐driven growth has been reported in diverse areas of crystallization—and indeed extensions of the Burton–Cabrera–Frank spiral growth model exist—our proposed mechanism on the role of “hidden” polytetrahedral phases in assisting heterogeneous nucleation supports and expands upon recent reports, for instance, metastable quasicrystal‐induced nucleation yielding grain‐refined alloys, among other two‐step solidification pathways.…”
Section: Resultssupporting
confidence: 70%
“…The case m ¼ 6 is also interesting, insofar as a cyclic twin nucleation has been reported to occur in tin-based solder alloys (Lehman et al, 2010), which strongly resembles the cyclic twin nucleation phenomena observed for NiZr (Hornfeck et al, 2018), yet differs in that the symmetry of the twin is sixfold.…”
Section: The Case M =mentioning
confidence: 78%
“…The twin model of NiZr was constructed by adhering to certain geometrical constraints imposed by NiZr's crystal structure (Hornfeck et al, 2014). Its parametrization by the spiral sequence of equation ( 33) followed only afterwards (Hornfeck et al, 2018;Hornfeck, 2018) and by empirically finding the suitable integer sequences for the baseline and alternating part in the On-line Encyclopedia of Integer Sequences (OEIS; Sloane, 2018). This has several drawbacks.…”
Section: A3 Inclination Function As a Binary Case Distinctionmentioning
confidence: 99%
See 2 more Smart Citations